Toward effective CSR communication in controversial industry sectors. Issue 3 (2nd April 2020) - Song, Baobao; Wen, Jing; Ferguson, Mary Ann
ABSTRACT: This study is aimed to unveil the effects of philanthropic corporate social responsibility (CSR) programs on consumers' perceptions toward CSR communication from corporations in 'issue-riddled' controversial industries, compared to noncontroversial industries. Particularly, this study examines how industry sector controversy, corporate reputation, and CSR company-cause fit jointly affect the outcomes of CSR communication. A total of 307 participants participated in a 2 × 2 × 2 between-subjects factorial experiment. The study finds that corporate reputation interacts with industry sector to influence consumers' attitude and behavioral intention. The effects of company-cause fit on CSR outcomes are overshadowed by corporate reputation and industry sector. This study implies that CSR communication could shorten the attitude gap between corporations in controversial and noncontroversial industries. More importantly, compared to employing specific communication tactics, maintaining good corporate reputation is more important for corporations in controversial industry sectors to enhance communication effectiveness. For companies with good corporate reputation in controversial industries, shifting reputation management strategy to industry reputation management can improve the effectiveness of CSR communication.